Analysis of Online Learning Problems in Social Studies Subjects (Scope of Elementary Schools) - Agnes Agustina; Desi Tamala; Lisna Yanti; Maulia Sari; Laurensia Masri Perangin Angin (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
At the beginning of 2020, the country of Indonesia was hit by a virus outbreak that we often know as COVID-19. This greatly affects all sectors in Indonesia, especially in the field of education. That is why, the rate of education in this pandemic era is very low. Even so, the Indonesian government always tries to advance education by issuing programs that help Indonesian students to keep learning. For example, by publishing online learning programs (on the network) as well as student quota funds or fees. Although it doesn't run like normal learning in general, this program might help a little. Unfortunately, the consequences of this program also cause many problems or problems that occur. Both internal and external factors. Social studies learning is one of the fields of study that includes social sciences, humanities and social problems of life. At the elementary school level, this learning is one of the important areas to learn, but since learning is done online, there are many things that create an obstacle in this learning. Therefore, it is necessary to solve problems in elementary social studies learning barriers to help realize the importance of social studies learning.